The Development of Mathematicâs Learning Tools of VIII Grade Based on Curriculum 2013 on The Quadratic Equation Subject - Afriyani, Lina; Zulkarnain, Zulkarnain; Nufus, Hayatun (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this research is to develqo the learning tools of mathematic on VIII grade based on curriculum 2013 in order to make a bridge of communication between teacher and student.The background of this research was based on unavailable the clear example about the development of learning tools based on curriculum 2013. The design of this learning tools consist of four meetings on quadratic equation subject.This study following the steps of the research development those are defining, planning, and developing. The technique of collecting data was descriptive qualitative, where the researcher revised based on the notes given by validator. After obtaining a valid criterion that was given by validator, then conducted trials on small groups of 6-8 students.After being tested on small groups, the researcher revised the product to be the reasonable final product. The result of this research showed that the learning tools of mathematic that was developed had the good quality. Based on the result of the questionnaire, the respons of the students on using Student activity sheetswas good. According to the result of the research. The researcher can conslude that the learning tools of mathematic which had been developed was valid and practical